A Review on Pharmacological Potential of Medicago sativa Linn - Rani, Rashmi; Nain, Sumitra; Paliwal, Sarvesh (Current Traditional Medicine, 2024)
Background: Medicago sativa Linn. in Hindi, is called lasunghas, and in English, it is called alfalfa. It is a well-known crop of the Fabaceae family. Anyone can eat its sprouts as a salad vegetable. This plant has a wide range of uses as a feed crop and is tolerant to climate change. Objective: In this review, the authors discussed the active chemical constituents and pharmacological uses of Medicago sativa Linn. in various diseases. Methods: To compile this review, information is collected the research papers from different databases like Taylor & Francis, ResearchGate, Elsevier, PubMed, Wiley Online Library, and PMC. Results: Alfalfa has been shown to be an important origin of phytochemicals like amino acids, coumarins, alkaloids, carotenes, flavonoids, organic acids, digestive enzymes, phytosterols, saponins, phytoestrogens, phenolic compounds, polyamines, and a few other volatile organic compounds like ketones, terpenes, alcohols and furanoids. This plant is useful in CNS disorders, anxiety, oxidative stress, hepatotoxicity, inflammation, cancer, atherosclerosis, diabetes, burn wounds, vitiligo, reproductive system, myocardial infraction, bacteria, xanthine oxidase and metabolic syndrome. Conclusion: This review may be helpful in knowing of Medicago sativa Linn. with greater therapeutic potential for treatment of various diseases.
Keywords: chemical constituents